Why do patients with ‘primary care sensitive’ problems access ambulance services? A systematic mapping review of the literature - Ali R G Shaw; Sarah Purdy; Matthew J Booker (BMJ Open)
Objective Emergency ambulance use for problems that could be managed in primary care continues to rise owing to complex reasons that are poorly understood. The objective of this systematic review is to draw together published evidence across a variety of study methodologies and settings to gain a better understanding of why patients seek help from ambulance services for these problems.Design Systematic searches were undertaken across the MEDLINE, EMBASE, PsychINFO, CINAHL, Health Management Information Consortium and Health Management Information Service publication databases. Google Scholar, Web of Science, OpenSigle, EThOS and DART databases were also systematically searched for reports, proceedings, book chapters and theses, along with hand-searching of grey literature sources. Studies were included if they reported on findings examining patient, carer, health professional or service management interactions with ambulance services for primary care problems. All study methodologies and perspectives were of interest. Data were extracted, quality assessed and systematically mapped according to key findings through generation of an iterative framework.Results A total of 31 studies met inclusion criteria. Findings were summarised across 5 broad categories: factors associated with individual patients; actions of care-givers and bystanders; population-level factors; health infrastructure factors; challenges faced by health professionals. A number of subcategories were developed to explore these factors in more detail.Conclusions This review reports important factors that may impact on ambulance use for primary care problems across a global setting, including demographic measures associated with deprivation, minority status and individual social circumstances. Categorising ambulance calls for primary care problems as ‘inappropriate’ is context dependant and may be unhelpful. Potential implications for triage and risk management strategies are discussed.